Misi Rekonsiliasi: Misi Gereja Katolik dalam Memulihkan Martabat Manusia Pasca Kekerasan di Indonesia - Utomo, Kurniawan Madyo (Sekolah Tinggi Teologia dan Filsafat Widya Sasana, 2023)
Various forms of violence still occur in Indonesia. This violence brings suffering, both to the victims and the perpetrators. Essentially, violence destroys human dignity. The purpose of this research is to answer the question of what the Catholic Church should do to combat violence and restore human dignity affected by violent acts. The method applied in this research is a qualitative method using literature studies. By employing critical discourse analysis, the thoughts of theologians and Church documents regarding the mission of the Catholic Church in the reality of violence and injustice are carefully examined. This research finds that in the face of the reality of violence and injustice that destroys human dignity, the Catholic Church cannot remain silent; it is called to promote a mission of reconciliation. The Church must strive to show forgiveness to restore the dignity of both victims and perpetrators of violence. It also must engage in dialogue with followers of other religions to address issues of violence. In these ways, the Church presents God Himself, who forgives sinners and restores their dignity.